The Effect Of The Ecirr Learning Model On Students’ Critical Thinking Ability In Class Learning Activities - Siti Rohmah; Ahmad Qurtubi; Achmad Abdul Azis; Jumadi Jumadi; Yoseb Boari (Mudir : Jurnal Manajemen Pendidikan, 2023)
This study's goal was to find out how the ECIRR (elicit, confront, identify, resolve, and reinforce) learning model affected students' ability to think critically about running wave and stationary wave content. A quasi-experimental research design with a non-equivalent control group design was the methodology employed. The technique of purposive sampling was used to collect samples. With a significance level of 5% (α = 0.05), the Mann-Whitney U test is used for the hypothesis test. It can be concluded that the ECIRR learning model has an impact on students' critical thinking abilities if the findings of the hypothesis test H0 are rejected. According to the N-Gain test results, the experimental class's N-Gain, which is in the medium category, increased more than the control class's N-Gain, which is in the low category. According to student responses to the ECIRR learning model, the majority of pupils reported feeling interested.